PEMBELAJARAN JARAK JAUH BERBASIS TEKNOLOGI DAN KOMUNIKASI DI SDN TANJUNG GUNUNG SINDUR - Ika Ika; Ade Muhamad Irfan; Ahmad Heru; Safitri Safitri (el-Moona: Jurnal Ilmu Pendidikan Islam, 2022)
This research was conducted to find out the benefits of information technology media in teaching and learning activities in elementary schools inn Gunung Sindur village. Considering the two years of learning using distance learning, namely learning online due to the imfact of exposure to covid-19 which has shaken the word, including our country, indonesia, which has felt the impact of all groups including the word of education, since march 2020 all indonesian education units have implemented dintance learning, at home, but white the advancement of information technology whice has developed rapidly at this time, information technologi can connect student white a teacher through E-learning media, whatsaap Groups, Google Classroom, Google froms, Google Meetings and Zoom application, so that at the elementary School level in yhe upper grades the application that is used is effective in teaching and learning avtivities using the classroom application, while for elementary schools in the lower grades the whatsaap group application can be used. Indistance learning activities, student cannot be spareted from the supervision of a teacher or a both parents